Improving the Properties of Clay Brick Using Polyvinyl Alcohol (PVA) - S. Abo Dhaheer, M.; H.K, Ammash; M.T, Albdiry (International Journal of Engineering and Technology, 2018)
In this study, an experimental research was dedicated to investigate the properties of clay brick treated by polyvinyl alcohol (PVA). Two methods of treatment were conducted. The first contained treating clay brick by submerging the specimens in 1%, 2% and 3% of PVA solution, whereas the second involved coating the brick specimens with 6% PVA (i.e. a high viscous solution). The treated specimens were allowed to dry under ambient temperature in the laboratory before being tested. Standard tests employed for brick specimens were applied. Regarding the specimens treated using the submerging method, results showed that there was a significant contribution of PVA to the compressive strength, total water absorption and efflorescence tests, in which the specimens reached the best performance when PVA was increased to 3%. However, the brick specimens coated by PVA showed a slight increase in the compressive strength, but a noticeable decrease in the water absorption and efflorescence.Â Â